Impaired thymic selection and abnormal antigen-specific T cell responses in Foxn1(Δ/Δ) mutant mice. - Shiyun Xiao; Nancy R Manley (PLoS ONE, 2010)
Foxn1(Δ/Δ) mutant mice have a specific defect in thymic development, characterized by a block in TEC differentiation at an intermediate progenitor stage, and blocks in thymocyte development at both the DN1 and DP cell stages, resulting in the production of abnormally functioning T cells that develop from an atypical progenitor population. In the current study, we tested the effects of these defects on thymic selection.We used Foxn1(Δ/Δ); DO11 Tg and Foxn1(Δ/Δ); OT1 Tg mice as positive selection and Foxn1(Δ/Δ); MHCII I-E mice as negative selection models. We also used an in vivo system of antigen-specific reactivity to test the function of peripheral T cells. Our data show that the capacity for positive and negative selection of both CD4 and CD8 SP thymocytes was reduced in Foxn1(Δ/Δ) mutants compared to Foxn1(+/Δ) control mice. These defects were associated with reduction of both MHC Class I and Class II expression, although the resulting peripheral T cells have a broad TCR Vβ repertoire. In this deficient thymic environment, immature CD4 and CD8 SP thymocytes emigrate from the thymus into the periphery. These T cells had an incompletely activated profile under stimulation of the TCR signal in vitro, and were either hypersensitive or hyporesponsive to antigen-specific stimulation in vivo. These cell-autonomous defects were compounded by the hypocellular peripheral environment caused by low thymic output.These data show that a primary defect in the thymic microenvironment can cause both direct defects in selection which can in turn cause indirect effects on the periphery, exacerbating functional defects in T cells.